2014
DOI: 10.1039/c4sc00674g
|View full text |Cite
|
Sign up to set email alerts
|

Lifetimes of carbocations encountered along reaction coordinates for terpene formation

Abstract: The lifetimes of secondary carbocations proposed to occur along reaction coordinates for terpene-forming carbocation rearrangements were estimated from direct dynamics simulations using density functional theory. Classical secondary carbocations supported by bicyclo[2.2.1] and bicyclo[2.2.2] frameworks have distinct characteristic lifetimes, ca. 40 and 90 fs, respectively. The fusion of additional rings to these frameworks was found to have little effect on these lifetimes, despite altering the potential energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 72 publications
(108 reference statements)
1
39
0
Order By: Relevance
“… 67 Enzyme-enforced conformational restriction (of reactant and subsequent species) clearly also plays a role in directing the reactant toward TSSs that are productive for epi -isozizaene formation and appears also to play a role in promoting the conversion of 4 to 5 to 6 . That leaves only fine-tuning to be ascribed to specific intermolecular electrostatic interactions (with OPP and/or active site aromatics) and/or effects of enzyme dynamics (rather than inherent substrate dynamics; tunneling may also play a role 37 ); these issues will be addressed in future quantum mechanical molecular mechanics (QM/MM) 68 70 and theozyme 18 , 71 73 studies on EIZS. Note how little is left to explain; while EIZS clearly plays keys roles in promoting pyrophosphate dissociation and preventing premature quenching of carbocations, we show here that its product distribution can be rationalized in large part on the basis of inherent carbocation reactivity and shape selection.…”
Section: Discussionmentioning
confidence: 99%
“… 67 Enzyme-enforced conformational restriction (of reactant and subsequent species) clearly also plays a role in directing the reactant toward TSSs that are productive for epi -isozizaene formation and appears also to play a role in promoting the conversion of 4 to 5 to 6 . That leaves only fine-tuning to be ascribed to specific intermolecular electrostatic interactions (with OPP and/or active site aromatics) and/or effects of enzyme dynamics (rather than inherent substrate dynamics; tunneling may also play a role 37 ); these issues will be addressed in future quantum mechanical molecular mechanics (QM/MM) 68 70 and theozyme 18 , 71 73 studies on EIZS. Note how little is left to explain; while EIZS clearly plays keys roles in promoting pyrophosphate dissociation and preventing premature quenching of carbocations, we show here that its product distribution can be rationalized in large part on the basis of inherent carbocation reactivity and shape selection.…”
Section: Discussionmentioning
confidence: 99%
“…These very low barriers prompted us to analyze the dynamical behaviour of system C in order to evaluate any differences with the concerted triple shift previously described and to predict the fate of 4*-H , a non-classical carbocation 8691. Thus, dynamics calculations were run for system C, starting from TS-1-2-H following the same methodology as previously used for system B.…”
Section: Resultsmentioning
confidence: 99%
“…TheIRC analysis clearly showed that TS1 connects 1b with 2b along ac oncerted but highly asynchronous pathway.I ndeed, the IRC showed ashoulder, suggesting the presence of ahidden intermediate,asituation often found when carbocations that are not stable enough to be characterized as minima are involved. [14] A geometrical analysis of the C9 environment during the reaction (see the Supporting Information) revealed the planarity (as expected for asp 2 -hybridization) of that center.T he formation of ac arbocationic species CB was confirmed by atopological analysis of the electron localization function (ELF), [15] which was used for monitoring the evolution of the electron population along the reaction coordinate (Figure 1, bottom). After point 60 of the IRC,the population of the C1-C2 and C4-C5 bonds increased, whereas those of C2-C3, C3-C4, C5-C6, and C6-C1 decreased.…”
mentioning
confidence: 75%
“…values. [14] A geometrical analysis of the C9 environment during the reaction (see the Supporting Information) revealed the planarity (as expected for asp 2 -hybridization) of that center.T he formation of ac arbocationic species CB was confirmed by atopological analysis of the electron localization function (ELF), [15] which was used for monitoring the evolution of the electron population along the reaction coordinate (Figure 1, bottom). Ther eaction starts through coordination of 3i to 1b (Figure 1, top).…”
mentioning
confidence: 99%